Resources, Events & Agents (REA) Sebagai Solusi Pada Siklus Pendapatan & Pengeluaran Kas : Tinjauan Empiris - Pratama, Bayu; Yuliansyah, Rahmat; Hartanti, Dian; Khaerul, Said; Amaliati, Desi; Krisnando, Krisnando; Shenurti, Elloni (Penerbit Goodwood, 2023)
Purpose: This writing aims to solve problems in one of the cycles in the accounting information system with the REA data model so that the management of the income and cash disbursement cycle is more effective and efficient. Method: Using qualitative methods with a case approach that occurred in the company. Primary data by conducting interviews with the object under study. As well as secondary data by documenting matters related to the income and expenditure cycle. Result: The results of the research are that the implementation of the income cycle has been running according to the specified function. However, the expenditure cycle is not running adequately. It is recommended for the application of cycles, companies can make plans for company goods and adjust cash records with established accounting standards. The cycle of income and cash disbursements in the documentation of cash receipts and cash outflows is not sequential, in which case it is recommended that the company plan a list of company goods and record cash in accordance with operating standards and procedures (SOP) and accounting standards and is equipped with regulations regarding punishment for office facilities misused by employees. Contribution: This research contributes to understanding the implementation and design of an accounting information system for the income and cash disbursement cycle using real data models in organizations. Limitation: The implementation of the Accounting Information System only covers the Revenue and Cash Expenditure cycles of the company that have been running so far.